2006
DOI: 10.1210/en.2005-1610
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Proliferator-Activated Receptor-γ Agonists Induce Partial Reversion of Epithelial-Mesenchymal Transition in Anaplastic Thyroid Cancer Cells

Abstract: Anaplastic thyroid cancer (ATC) is an extremely aggressive tumor characterized by marked epithelial mesenchymal transition, which leads, almost invariably, to death. Peroxisomal proliferator-activated receptor (PPAR)-gamma agonists have recently emerged as potential antineoplastic drugs. To establish whether ATC could be a target of PPAR gamma agonists, we first examined PPAR gamma protein expression in a panel of six ATC cell lines and then studied the biologic effects of two PPAR gamma agonists, ciglitazone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 48 publications
5
94
1
1
Order By: Relevance
“…The role oncogenes play in initiation of EMT-related changes and the roles of other EMT-related proteins, including osteopontin, RUNX2, and fibronectin 1 remain to be defined; however, recent evidence from in vitro models demonstrate that RET/PTC and BRAF influence the invasive capacity of benign rat thyroid cells through both PI3 kinase and ERK signaling, in part, through regulation of matrix metalloproteinases and osteopontin (16,32). Whereas we have studied a small panel of thyroid cancer cell lines, studies from other thyroid (33,34) and nonthyroid cancer cell systems support a role for incomplete or complete EMT as common endpoints in tumor progression (35). Additional studies are needed to determine the role of specific EMT regulators, such as vimentin, in a larger number of cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The role oncogenes play in initiation of EMT-related changes and the roles of other EMT-related proteins, including osteopontin, RUNX2, and fibronectin 1 remain to be defined; however, recent evidence from in vitro models demonstrate that RET/PTC and BRAF influence the invasive capacity of benign rat thyroid cells through both PI3 kinase and ERK signaling, in part, through regulation of matrix metalloproteinases and osteopontin (16,32). Whereas we have studied a small panel of thyroid cancer cell lines, studies from other thyroid (33,34) and nonthyroid cancer cell systems support a role for incomplete or complete EMT as common endpoints in tumor progression (35). Additional studies are needed to determine the role of specific EMT regulators, such as vimentin, in a larger number of cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…These antitumor effects have also been attributed to PPARg activation. There is evidence that PPARg agonists promote cell redifferentiation, which is reflected in the upregulation of specific differentiation markers (NIS, TSH receptor, LPO, and thyroglobulin) and downregulation of a dedifferentiation marker (CD97) in thyroid cancer (Park et al 2005, Aiello et al 2006. Additional experiments are required to confirm this hypothesis with respect to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In an initial study, Karger et al reported that mRNA for PPARγ is downregulated in papillary thyroid cancer cells [37], and Chung et al reported that troglitazone inhibits growth of anaplastic thyroid cancer cells [38]. Similar results have been consistently observed in other anaplastic or dedifferentiated thyroid cancer cells, that is, various thiazolinediones induce cell growth inhibition, cell cycle arrest, and apoptosis [39][40][41]. This activity is explicitly correlated with PPARγ activation because PPARγ-lacking thyroid cancer cells did not demonstrate such effects, and restoration of PPARγ resulted in restoration of response to thiazolinediones [39,42].…”
Section: Pparγ Agonistsmentioning
confidence: 73%
“…This activity is explicitly correlated with PPARγ activation because PPARγ-lacking thyroid cancer cells did not demonstrate such effects, and restoration of PPARγ resulted in restoration of response to thiazolinediones [39,42]. Interestingly, activation of apoptosis by thiazolinediones was not related to p53, but to p21 or p27 [38,39,41]. Besides growth inhibition and apoptosis activation, PPARγ agonists induce differentiation of thyroid cancer cells.…”
Section: Pparγ Agonistsmentioning
confidence: 99%